2007
DOI: 10.1534/genetics.106.064311
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci × Maternal Cytoplasmic Environment Interaction for Development Rate in Oncorhynchus mykiss

Abstract: Effects of maternal cytoplasmic environment (MCE) on development rate in rainbow trout were evaluated within a quantitative trait loci (QTL) analysis framework. Previous research had identified QTL for development rate in doubled haploid (DH) progeny produced from a cross between the Oregon State University (OSU) and the Swanson (SW) River rainbow trout clonal lines. In this study, progeny for QTL mapping were produced from a cross between the OSU and Clearwater (CW) River clonal lines. Doubled haploids were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 73 publications
6
68
1
Order By: Relevance
“…Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70]. Thus, this study supports previous suggestions that the LD block on chromosome Omy5 represents a 'master control region' influencing residency and anadromy in O. mykiss [46,72] and is a parallel selected region [21] that has experienced repeated selection in multiple populations.…”
Section: Discussionsupporting
confidence: 87%
“…Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70]. Thus, this study supports previous suggestions that the LD block on chromosome Omy5 represents a 'master control region' influencing residency and anadromy in O. mykiss [46,72] and is a parallel selected region [21] that has experienced repeated selection in multiple populations.…”
Section: Discussionsupporting
confidence: 87%
“…In rainbow trout, studies have variously identified QTL of major and minor effect for hatch timing. Nichols et al (2007) identified six minor QTL for hatch timing, one of which was located on rainbow trout linkage group RT14 (termed OC-14 in Nichols et al, 2007). In this study the QTL for hatch timing was associated with marker Omm1241 that has been mapped to OKI14, the coho linkage group homologous to RT14 (McClelland and Naish, 2008).…”
Section: Ek Mcclelland and Ka Naishmentioning
confidence: 65%
“…Second, randomization in permutation tests removes the main effect of the QTL, as well as its interaction with the environment, and so assumes that the probability distribution for G 3 E interactions is the same in the absence as in the presence of a QTL (cf. Nichols et al 2007), which may not be the case.…”
Section: Methodsmentioning
confidence: 96%